Hemodynamic rounds : interpretation of cardiac pathophysiology from pressure waveform analysis - Kern, Morton J.; Lim, Michael J.; Goldstein, James A. (Wiley Blackwell, 2018)
"The essential resource on cardiac hemodynamics--now in a new edition Hemodynamic Rounds, Fourth Edition is intended to help cardiologists, cardiovascular fellowship trainees, residents and other members of the medical community enhance their understanding of cardiac physiology and its associated hemodynamic presentations in health and disease. This includes the basic principles of flow and pressure measurements, systemic as well as coronary hemodynamics in normal and diseased states, and changes in hemodynamics following interventional procedures ranging from TAVI and valvuloplasty to stent placement. Like its popular predecessors, this new edition draws on case studies to illustrate characteristic cardiac hemodynamic findings and discusses the essential methods used in interpreting pressure waveforms as a diagnostic and monitoring tool. The text is organized into chapters on specific areas of the heart, common cardiac pathophysiologic conditions, and hemodynamic situations resulting from different therapeutic procedures. It includes discussions of both normal and abnormal pressure waveforms. This new edition has been revised throughout to include brand new content on aortic and mitral valve stenosis and regurgitation as well as TAVI and mitral clip hemodynamics. Highlights include: Essential and easy to understand resource for those required to interpret cardiac blood flow and blood pressure tracings Covers hemodynamic assessment by cardiac disorder, plus the bedside applications of hemodynamics Revised throughout and includes brand new content on valve stenosis and regurgitation and TAVI and mitral clip hemodynamics Hemodynamic Rounds: Interpretation of Cardiac Pathophysiology from Pressure Waveform Analysis, Fourth Edition is an indispensable tool for all physicians, nurses, and students responsible for measuring and interpreting cardiac waveforms in cardiac diagnosis and monitoring"--Provided by publisher.